The impact of adherence on costs and effectiveness of telemedical patient management in heart failure - Hameed, A. S.; Sauermann, S.; Schreier, G. (Applied Clinical Informatics, 2014)
Objective: This paper analyzes evidence of the impact of patients’ adherence to pharmacological and non-pharmacological recommendations on the treatment costs of heart failure (HF) patients.Methods: A systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Papers were searched using various combinations of the following keywords: ‘telemedicine’, ‘telemonitoring’, ‘telehealth’, ‘eHealth’, ‘remote monitoring’, ‘adherence’, ‘compliance’, ‘cost-effectiveness’, ‘cost-benefit’, ‘heart failure’, ‘healthcare costs’, ‘hospitalization’, and ‘drug costs’. We included only papers written in English or German, published between 1998 and 2014, and having one of our search terms in the title.Results: Initially, 73 papers were selected. After a detailed review, these were narrowed done to 9 that reported an association between adherence and/or compliance and costs. However, none established a quantitative relationship between adherence and total healthcare costs.Conclusion: A model-based cost-effectiveness analysis that appropriately considers adherence has not been carried out so far, but is needed to fully understand the potential economic benefits of telehealth.Citation: Hameed AS, Sauermann S, Schreier G. The impact of adherence on costs and effectiveness of telemedical patient management in heart failure: A systematic review. Appl Clin Inf 2014; 5: 612–620http://dx.doi.org/10.4338/ACI-2014-04-RA-0037
Keywords: Telemedicine; mHealth; therapy adherence/compliance; cost-effectiveness; heart failure